Bioencapsulation for Smart Delivery of Agriculturally Important Microorganisms - E, Sheeza T (Indian Farming, 2020)
Beneficial microbes are available in different formulations, the common types being liquid, peat, granules, and freeze-dried powders. Nevertheless, a promising advancement would be to develop techniques that allow encapsulating the microbial strain in a nutritive shell or capsule and deliver them to the targeted site. This would ensure precision delivery, lower application, easy handling and cost-effectiveness. Hence, a major area of focus was development of novel delivery systems of bacteria and fungi for growth promotion, soil nutrient solubilisation and biocontrol.